Coexistence of a novel NBEA-ALK, EML4-ALK double-fusion in a lung adenocarcinoma patient and response to alectinib: A case report. (December 2021) - Liang, Qi; Xu, Huanhuan; Liu, Yiqian; Zhang, Weiming; Sun, Chongqi; Hu, Meng; Zhu, Yizhi; Tan, Shanyue; Xu, Xian; Wang, Sumeng; Liu, Lingxiang
Highlights: This is the first report on one patient with a novel NBEA-ALK, EML4-ALK double-ALK fusion beneficial from alectinib. NBEA-ALK (N5:A20) has never been reported previously. Alectinib could be a viable therapeutic option for NSCLC patients with double-ALK fusion. Initial NGS detection is crucial to follow-up treatment while liquid biopsy can dynamically monitor clinical curative effect. Abstract: Objectives: The echinoderm microtubule-associated protein-like 4 gene (EML4) and anaplastic lymphoma kinase gene (ALK) fusion is the most common ALK rearrangements in non-small cell lung cancer (NSCLC). Herein, we firstly report that coexistence of a novel Neurobeachin (NBEA)-ALK, EML4-ALK double-fusion is sensitive to alectinib. Materials and methods: Hematoxylin-eosin staining (HE), fluorescent in situ hybridization (FISH), and next-generation sequencing (NGS) was performed on the biopsy sample. Results: The patient responded to alectinib as a second-line treatment and achieved stable disease for 11 months, without significant symptoms of toxicity. Significantly, the liquid biopsy also validated clinical benefit, with the disappearance of NBEA-ALK and EML4-ALK fusion variants. We also provided a comprehensive review of all 50 ALK fusion genes in NSCLC. Conclusion: This is the first report on one patient with a novel NBEA-ALK, EML4-ALK double-ALK fusion beneficial from alectinib. Alectinib may be a viable therapeutic option for NSCLC patients with double-ALK fusion, and liquid biopsy could dynamically monitor clinical curative effect.